Kelayakan Pantai Tanjung Pinggir Sekupang Kota Batam Sebagai Lokasi Rukyatul Hilal - Angkat, M. Arbisora; Taufiq, M.; Hidayatulah, Rizki Pradana; Triputra, Muhammad Abid; Fornandes, Yangga; Herlambang, Bagus Sindhu (TERAJU: Jurnal Syariah dan Hukum, 2023)
The basis for considering Tanjung Pinggir Sekupang Beach as location for hilal sighting started from visiting of Hisab Rukyat Division from Jakarta to Batam City Ministry of Religion during Hisab Rukyat Training in 2016. After observations at various locations according to them, this beach is considered suitable as a location for hilal sighting because from the height of the place it is sufficient. After further research, Tanjung Pinggir Sekupang Beach is not supported by primary parameters, because geographically it is blocked by buildings, small islands and trees at azimuth 240o-300o. Meanwhile, the weather conditions are also not supportive, because Batam City has low air temperature, humidity and high rainfall, causing Batam City to be more often in cloudy weather conditions and categorized as a wet month criteria. This is also supported by the results of hilal sighting report from Hisab Rukyat Team of Batam City which always fail to see the hilal from 2016-2022 due to weather factors. Tanjung Pinggir Sekupang Beach is supported by secondary parameters, because in terms of accessibility and beach facilities this is quite adequate. Because Tanjung Pinggir Sekupang Beach is not supported by primary parameters and supported by secondary parameters, this beach is in the category of less suitable as a location for hilal sighting.